On dubious claims regarding the enigmatic Chilston. Issue 1 (April 2022) - ALDEN, JANE; CALLAGHAN, LYNSEY
ABSTRACT: The earliest known treatise on Boethian proportions in Middle English is attributed to 'Chilston' in London, British Library, Lansdowne 763. Nothing is known of Chilston's biography, although his treatise also survives anonymously in two related sources (New York, Morgan Library, B.12 and Dublin, Trinity College, 516). In 1927, Irish musicologist William Henry Grattan Flood suggested an identification between the author of the proportion treatise and the scribe of British Library, Royal 5 A VI, a priest's handbook dated to 1446. English lexicographer Jeffrey Pulver was quick to dismiss Flood's identification, which apparently discouraged any further assessment of it. This article reconsiders Flood's suggestion, taking into account 1920s political and cultural biases that might explain Pulver's swift rejection. A contextual exploration of the evidence supports the connection of the proportion treatise to Royal 5 A VI and sheds light on the milieu in which Chilston may have worked. Long recognised for his significance in the vernacular history of music theory and music pedagogy, the proposed contextual framework has significant implications for understanding the multiple functions of music theory in fifteenth-century England. Most notably, it documents the use of speculative music theory among readers and audiences with limited knowledge of Latin. A variety of uses for music theory reveal themselves within the emerging vernacular pedagogical practices of late medieval England. These reflect the broader production of technical texts in Middle English and the increased vernacularisation of English society at a pivotal moment of ecclesiastic and musical history.